Anisotropic localized surface plasmon resonance of vanadium dioxide rods in flexible thermochromic film towards multifunctionality - Xu, Qiyang (2022)
Plasmonic thermochromic films are promising for smart window applications. Hereby, we develop a flexible plasmonic thermochromic film towards multifunctionality. The double-layer film consists of a bottom layer of W/Mg co-doped vanadium dioxide (VO2) rods in a polyurethane acrylate matrix and a top layer of hollow silica spheres (HSSs). Based on the finite-difference time-domain (FDTD) method, we demonstrate for the first time, a transverse and a longitudinal mode of VO2 localized surface plasmonic resonance (LSPR) in near- and mid-infrared bands, respectively, and only the transverse mode contributes to the solar energy modulation performance. The film shows a luminous transmittance of 46.2%, a solar energy modulation of 10.8%, and a critical transition temperature of 36.9 °C. The HSSs overcoating enhances the surface hydrophilicity and thermal insulation, which give rise to more favored functionalities for windows.